Neurotoxic effects of selected metals. - Wennberg, Arne (Scandinavian Journal of Work, Environment & Health, 1994)
A chemical is considered to be neurotoxic if it is capable of inducing a consistent pattern of neural dysfunction or lesion in the nervous system. Several metals are known as neurotoxic. Among them, four have been selected as being especially important from the occupational point of view, lead, manganese, aluminium, and mercury. All four have proved to be neurotoxic even though the toxic mechanisms may be unclear or unknown. This paper reviews the recently published documentation on the neurotoxic properties of these metals, from the general as well the occupational point of view.